The Dual Impact of HIV-1 Infection and Aging on Naïve CD4+ T-Cells: Additive and Distinct Patterns of Impairment - Rickabaugh, Tammy M.; Kilpatrick, Ryan D.; Hultin, Lance E.; Hultin, Patricia M.; Hausner, Mary Ann; Sugar, Catherine A.; Althoff, Keri N.; Margolick, Joseph B.; Rinaldo, Charles R.; Detels, Roger; Phair, John; Effros, Rita B.; et al. (PloS one, 2011)
HIV-1-infected adults over the age of 50 years progress to AIDS more rapidly than adults in their twenties or thirties. In addition, HIV-1-infected individuals receiving antiretroviral therapy (ART) present with clinical diseases, such as various cancers and liver disease, more commonly seen in older uninfected adults. These observations suggest that HIV-1 infection in older persons can have detrimental immunological effects that are not completely reversed by ART. As naïve T-cells are critically important in responses to neoantigens, we first analyzed two subsets (CD45RA(+)CD31(+) and CD45RA(+)CD31(-)) within the naïve CD4(+) T-cell compartment in young (20-32 years old) and older (39-58 years old), ART-naïve, HIV-1 seropositive individuals within 1-3 years of infection and in age-matched seronegative controls. HIV-1 infection in the young cohort was associated with lower absolute numbers of, and shorter telomere lengths within, both CD45RA(+)CD31(+)CD4(+) and CD45RA(+)CD31(-)CD4(+) T-cell subsets in comparison to age-matched seronegative controls, changes that resembled seronegative individuals who were decades older. Longitudinal analysis provided evidence of thymic emigration and reconstitution of CD45RA(+)CD31(+)CD4(+) T-cells two years post-ART, but minimal reconstitution of the CD45RA(+)CD31(-)CD4(+) subset, which could impair de novo immune responses. For both ART-naïve and ART-treated HIV-1-infected adults, a renewable pool of thymic emigrants is necessary to maintain CD4(+) T-cell homeostasis. Overall, these results offer a partial explanation both for the faster disease progression of older adults and the observation that viral responders to ART present with clinical diseases associated with older adults.